X-band digitization systems aspects and filters for MeerKAT radio astronomy receiver - Malan, Jocias A (Department of Electrical Engineering, 2018)
The MeerKAT Radio Telescope is a 64 element antenna array under construction in South Africa. This array will be used to observe radiation from celestial sources at radio frequencies. Once completed, this radio telescope will be the largest and most sensitive radio telescope in the Southern hemisphere. MeerKAT is being designed to observe radio signals produced by celestial sources at UHF-, L-, S- and X-band frequencies. With the development of the X-band receivers for MeerKAT scheduled to start in the near future, research is required to determine an optimum receiver design for this frequency band. There are two architecture options available for digitization of this band namely direct digitization of the entire band or digitization of a portion of the frequency band using a heterodyne configuration. In this thesis, both these options are investigated to determine the feasibility of both these architectures. A key outcome of this investigation will be the derivation of the specifications of the anti-aliasing filter used in a direct digitization receiver as well as the image reject filter used in the heterodyne receiver. The design of a wideband microwave filter capable of meeting these specifications is also presented. To conclude this investigation, the impact of the designed filter on the performance of the system is presented.